2020
DOI: 10.3366/scot.2020.0331
|View full text |Cite
|
Sign up to set email alerts
|

Stay or Go? – Roma, Brexit and European Freedom of Movement

Abstract: The spectre of Brexit has raised issues of concern for Roma communities living and working in Scotland and other parts of the UK. The effective ending of freedom of movement has produced new uncertainties and insecurities for people living outside their EU countries of origin, especially for those who are racialised and stigmatised by ‘hostile environment’ policies. Brexit is best understood as both a process and effect of everyday bordering as well as a continuation of historically embedded structural divisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In a detailed analysis of the Brexit referendum, Sobolewska and Ford (2020, 281) have found that "negative views of migrants and minorities were (and are) roughly as widely held in Scotland as in England and Wales, but they were ignored by the SNP, who directed ethnocentric voters' resentments towards London and the Tories" (2020, p. 281). Moreover, in Glasgow, Clark (2020) has reported that discrimination against Scotland's largest Roma minority migrant groups (of EU membership country origin) in the Govanhill area has increased in recent years. These developments also illustrate that there is a "disjunction between pro-migration rhetoric and anti-immigration sentiments at population level" in Scotland (Sime 2020, 337).…”
Section: Pro-immigration Discourse and Scottish Civic Nationalismmentioning
confidence: 99%
“…In a detailed analysis of the Brexit referendum, Sobolewska and Ford (2020, 281) have found that "negative views of migrants and minorities were (and are) roughly as widely held in Scotland as in England and Wales, but they were ignored by the SNP, who directed ethnocentric voters' resentments towards London and the Tories" (2020, p. 281). Moreover, in Glasgow, Clark (2020) has reported that discrimination against Scotland's largest Roma minority migrant groups (of EU membership country origin) in the Govanhill area has increased in recent years. These developments also illustrate that there is a "disjunction between pro-migration rhetoric and anti-immigration sentiments at population level" in Scotland (Sime 2020, 337).…”
Section: Pro-immigration Discourse and Scottish Civic Nationalismmentioning
confidence: 99%
“…In a detailed analysis of the Brexit referendum, Sobolewska and Ford (2020, 281) have found that "negative views of migrants and minorities were (and are) roughly as widely held in Scotland as in England and Wales, but they were ignored by the SNP, who directed ethnocentric voters' resentments towards London and the Tories" (2020: 281). Also, in Glasgow, Clark (2020) has reported that discrimination against Scotland's largest Roma minority migrant groups (of EU membership country origin) in the Govanhill area has increased in recent years. These developments also illustrate that there is a "disjunction between pro-migration rhetoric and anti-immigration sentiments at population level" in Scotland (Sime 2020, 337).…”
Section: Pro-immigration Discourse and Scottish Civic Nationalismmentioning
confidence: 99%